INVESTIGATION OF Cu, Mn OR Ti ION SUBSTITUTIONS ON THE MICROWAVE ABSORBANCE PROPERTIES OF BARIUM HEXAFERRITE - Sebayang, Perdamean; Sari, Ayu Yuswita; Ginting, Masno; Ginting, Riski Titian (LIPI Press, 2014)
The influence of Cu, Mn or Ti ion substitution on the microwave absorbance properties of Barium M-Hexaferrite (BaFe12O19) has been investigated. The sample preparation was held by mixing the raw material of Copper oxide (CuO), Manganese oxide (MnO) or Titanium dioxide (TiO2) with a different composition into BaFe12O19 powder through ball milling process, then sintered at 1100oC for 2 h. The substitution composition for each metal ion (Cu, Mn or Ti) into BaFe12O19 powder was 0.1 and 0.5 % mol. The Vector Network Analyzer (VNA) measurement was used to determine the reflection loss and absorption properties of BaFe12O19 samples within frequency ranging from 410 GHz. The minimum reflection loss 20.3 dB at 4 GHz was achieved, which is related to the 0.1% mol of Ti substitution on BaFe12O19 sample. The reflection loss values could be modified by controlling the metal ions composition which consequently improves the microwave absorption properties. The complex permittivity and permeability were calculated using Nicholson-Ross Weir (NRW) method. The peak of real and imaginary parts of permittivity was consistently appeared at 5.05, 5.92, 6.76, and 7.75 GHz for all metal ions (Cu, Mn and Ti). Furthermore, the complex permeability was found to be independent from frequency and the ion substitution did not significantly influence hexagonal structure and particle size distribution of Barium hexaferrite.